Items to be considered in reviving the forest sector development models for Peninsular Malaysia - Hadi, Yusuf; Abd Rahim, Abd Rahman (1987)
Certain aspects of the model and the types of computer to consider in the revival of the Peninsular Malaysia Forest Sector Development Models are discussed. A strategy in the model should incorporate the size of the Permanent Forest Estate (PFE) as a major component, the conversion of the Stateland Forest (SLF) as a short-term additional source of logs, and cutting cycles and harvesting intensities that should be interrelated and in accordance with the practice of the Selective Management System. The model should continue to calculate log production only from the inland forest but should add to this the productions of other fibre resources such as mangrove, rubberwood, forest plantation materials, residues and import to be used in subsequent phases of calculation. Log production should be calculated initially for the whole peninsula and then for each of the states. The forest data should be organised by forest reserves and compartments for peninsula and state-level planning, respectively. The planning horizon of 20 years, divided into four 5-year planning periods should be maintained but the values of parameters for the first period should be expressed on an annual basis to indicate the short-term scenario. The long term perspective should be analysed and reported in greater detail. Strategy should be selected such that a continuous log production sufficient for the requirements of the processing mills and domestic consumption is achieved. The values of selected socio-economic parameters could then be estimated from that level of log production. The mathematical programming model should use actual locations of forest compartments, towns, ports and mills for primary and downstream processing. Both models should be written and run on microcomputers because of the wide availability and rapid developments in microcomputer hardware and software.